The Impact of Self-Efficacy and Employee Mutation on Employee Performance - Rahmatika, Ajeng Dian; Kustini, Kustini (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
This study investigates the influence of self-efficacy and employee turnover on employee performance at PT. PLN (Persero) UP2B East Java. Employing a quantitative research design, data was analyzed using Smart PLS software. Given the small population size, a census sampling method was applied, encompassing all 69 employees. Data collection was conducted through observations, interviews, and questionnaires. The analysis included tests for validity and reliability, R-Square evaluation, and hypothesis testing via bootstrapping. The results reveal that both self-efficacy and employee turnover positively influence employee performance. Employees with higher self-efficacy demonstrate superior job performance, and increased employee turnover is also linked to improved performance.